(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Rheumatoid arthritis (RA) is a chronic systemic autoimmune inflammatory disease of connective tissues, which occurs mainly in the form of erosive-destructive polyarthritis with an exacerbation of perivertebral joints.